Reprogrammed CD4+ T Cells That Express FoxP3+ Control Inhibitory Antibody Formation in Hemophilia A Mice - Herzog, Roland W.; Kuteyeva, Veronica; Saboungi, Rania; Terhorst, Cox; Biswas, Moanaro (Frontiers in Immunology, 2019)
Coagulation Factor VIII (FVIII) replacement therapy in hemophilia A patients is complicated by the development of inhibitory antibodies, which often render the treatment ineffective. Previous studies demonstrated a strong correlation between induction of regulatory T cells (Treg) and tolerance to the therapeutic protein. We, therefore, set out to evaluate whether the adoptive transfer of FVIII-specific CD4+ Treg cells prevents inhibitor response to FVIII protein therapy. To this end, we first retrovirally transduced FoxP3+ into FVIII-specific CD4+ cells, which resulted in cells that stably express FoxP3, are phenotypically similar to peripherally induced Tregs and are antigen specific suppressors, as judged by in vitro assays. Upon transfer of the FVIII-specific CD4+ FoxP3+ cells into hemophilia A mice, development of inhibitory antibodies in response to administering FVIII protein was completely suppressed. Suppression was extended for 2 months, even after transferred cells were no longer detectable in the secondary lymphoid organs of recipient animals. Upon co-transfer of FoxP3+-transduced cells with the B cell depleting anti-CD20 into mice with pre-existing inhibitory antibodies to FVIII, the escalation of inhibitory antibody titers in response to subsequent FVIII protein therapy was dramatically reduced. We conclude that reprogramed FoxP3 expressing cells are capable of inducing the in vivo conversion of endogenous FVIII peripheral Tregs, which results in sustained suppression of FVIII inhibitors caused by replacement therapy in recipient hemophilia A animals.